Problem solving and project management: optimization proposal for the metalworking sector in São Paulo - Picon, André Belasques Ruiz; Manoel (Brazilian Journal of Production Engineering, 2021)
Problems happen daily within organizations and in the daily life of project managers. The way to deal with these problems is not always done considering systematic, well-structured and project management methodologies. However, the objective of this research was to identify in the literature the main problem-solving methodologies, collect information in the São Paulo metal-mechanical sector about how they are managed and to propose an approach from the perspective of project management. The method has a quantitative approach and the technical procedure for data collection was carried out using a questionnaire using a Likert scale. The data collected allowed an analysis of how problems are handled by the focus universe of study and they demonstrated a need for better tools to plan how to carry out activities. Nevertheless, the real and main contribution of this research is the proposal to implement an approach based on the “Lean Manufacturing” philosophy using “canvas” as ways to optimize the industrial production process to solve problems in a structured way.
Keywords: Project Management; Problem solving; Lean Manufacturing